Competition Among Banks: Introduction and Conference Overview - Allen, Franklin; Gersbach, Hans; Krahnen, Jan-Pieter; Santomero, Anthony M. (Review of Finance, 2001)
Franklin Allen, Hans Gersbach, Jan-Pieter Krahnen, Anthony M. Santomero; Competition Among Banks: Introduction and Conference Overview, European Finance Re